Extending the scope of configuration management for the development and life cycle support of systems of systems—An ontology‐driven framework applied to the Enceladus Submarine Exploration Lander. Issue 3 (8th March 2020) - Kossmann, Mario; Samhan, Ahmad; Odeh, Mohammed; Qaddoumi, Eman; Tbakhi, AbdelGhani; Watts, Stephen
Abstract: Increasingly complex systems of systems (SoS) have to be developed in ever shorter times‐to‐market at reduced costs and with high reliability. In addition, as the life cycle of such SoS frequently spans across several decades, customer expectations and market conditions will evolve. Systems engineering (SE)/model‐based systems engineering (MBSE) and configuration management (CM) need to be ever more closely integrated to appropriately address this situation. CM as a discipline is essential for establishing traceability and controlling baseline evolutions between all the relevant pieces of information resulting from the related system life cycle processes of all constituent systems of such SoS; but for this to work, the scope of CM must be extended both throughout the entire life cycle and across all participating monolithic systems. New frameworks are needed to effectively and efficiently apply CM across SoS arrangements. This paper proposes an ontology‐based, federative approach to managing the inherent complexity of CM in the context of SoS, with particular focus on a change management framework for SoS. Examples from a conceptual system that is concerned with the submarine exploration of Enceladus as part of the "Saturn exploration system" are used to demonstrate typical SE/MBSE artifacts and how CM needs to address them across the involved operational and enabling systems.